Effect of obstructive sleep apnoea syndrome combined with renal insufficiency on all-cause mortality in elderly patients in China: a prospective cohort study - Lin Liu; Zhe Zhao; Yinghui Gao; Fengfeng Fang; Zuo Zhang; Libo Zhao; Zijun He; Kailiang Li; Hongyan Bian (BMJ Open)
Objective We hypothesised that all-cause mortality in elderly patients with obstructive sleep apnoea syndrome (OSAS) was associated with renal insufficiency.Design A cohort study.Setting A prospective study of patients with OSAS enrolled in sleep centres/departments in multicentre hospitals in China from 2015 to 2017.Participants A total of 1290 patients with OSAS from six tertiary comprehensive hospitals in China were included in this study; of these, 1076 patients were included in the analysis based on inclusion and exclusion criteria.Main outcome measures All-cause death events were the main adverse outcomes.Result During a median follow-up of 42 months, 50 patients (4.6%) died, including 24 (2.2%) cardiovascular deaths. The incidence of all-cause death and cardiovascular death was higher in patients with estimated glomerular filtration rate (eGFR) less than 30 mL/min/1.73 m2 than in the other groups (p<0.001). Multivariate Cox regression models showed that patients with low levels of eGFR had a higher risk of all-cause death compared with patients with high levels of eGFR (HR=8.954, 95% CI, 2.108 to 38.033; p=0.003) and cardiovascular death risk (HR=4.163, 95% CI, 1.524 to 11.375; p=0.005).Conclusion The incidence of all-cause death and cardiovascular death events increased with decreasing renal function in elderly patients with OSAS and was higher in patients with end-stage renal insufficiency. The risk of all-cause and cardiovascular deaths was highest at eGFR below 30 mL/min/1.73 m2.